Effects of Periplaneta americana extracts on the growth and proliferation of cutaneous interstitial cells in cutaneous-wound healing - Liang, Zheng; Han, Guiqi; Luo, Zecheng; Li, Baojie; Liu, Wentao; Shen, Chongyang (Frontiers in Pharmacology, 2022)
Rapid and effective cutaneous wound healing requires a coordinated response of multiple cells including Mesenchymal Stromal Cells. Impaired healing of cutaneous wounds can lead to a variety of adverse health outcomes. Periplaneta americana extracts Kangfuxin (KFX) play a crucial role in cutaneous wound healing. Herein, the dermal cells of sucking mice were isolated and a mouse model of cutaneous injury was established for in vitro and in vivo studies, respectively. KFX treatment induced the proliferation and migration of Mesenchymal Stromal Cells and wound healing in the animal model. Furthermore, the effects of KFX on wound healing were found to depend on the signal transducer and activator of transcription 3 (STAT3) signaling pathway. Our studies provide the theoretical and clinical basis underlying the role of KFX in cutaneous wound healing.